2015
DOI: 10.14202/vetworld.2015.453-460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of lysine producing microbes vis-a-vis source and level of dietary protein on performance and egg quality characteristics of post-peak layers

Abstract: Aim:The aim was to study the effect of supplementation of lysine producing microbes (LPM) as an in vivo source of lysine on performance and egg quality characters of post-peak layers.Materials and Methods:BIS (1992) specified diets (except crude protein [CP] and lysine) were prepared using either soybean meal (SBM) or groundnut extractions (GNE) or sunflower extractions (SFE) with 16 and 15% CP resulting in six control diets. Further, each control diet was fortified with either synthetic lysine or LPM to meet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Level values of crude protein, methionine, and lysine are not affected by the addition of garlicon. This was taken into account due the important role they play in laying hen feed [ 29 ]. Moreover, methionine and lysine could influence egg weight results [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Level values of crude protein, methionine, and lysine are not affected by the addition of garlicon. This was taken into account due the important role they play in laying hen feed [ 29 ]. Moreover, methionine and lysine could influence egg weight results [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although several analytical methods for PTSO determination have been established for feed [ 25 , 29 ] or milk [ 43 ], PTSO has not been determined as a residue in egg samples. In order to establish a methodology for controlling the sensory attributes of eggs, a new method to analyze PTSO and its derivatives was required.…”
Section: Methodsmentioning
confidence: 99%
“…Observations on the egg production performance of layer Japanese quails fed low crude protein diet supplemented with lysine are similar to the findings of Demuner et al (2009a, b) who evaluated the nutritional requirements of digestible lysine for Japanese quails at the laying phase. Contrary to this, Garcia et al (2005) and Manju et al (2015) obtained lower egg production with 16% CP which may be as result of inadequate quantity of amino acid in the diet while Bunchasak et al (2005) also reported poor egg production, egg weight and egg mass from birds that received 14% CP. Similar to the result of this study, Murakami et al (1993) had earlier observed a nonsignificant effect of dietary protein level on feed intake of Japanese quails.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 85%
“…Studies on the effects of dietary Ca on egg quality were mainly concerned with eggshell quality (An et al, 2016;Chang et al, 2019). Calcium is the most important mineral in eggshells and is also responsible for the internal quality of eggs (Manju et al, 2015;Chang et al, 2019). Eggshell is a sophisticated bio-ceramic structure consisting of calcium carbonate (CaCO 3 ), crystals (approximately 98%), and an organic protein matrix (Gautron et al, 2021;McClelland et al, 2021).…”
Section: Introductionmentioning
confidence: 99%